2015
DOI: 10.3758/s13414-015-1042-y
|View full text |Cite
|
Sign up to set email alerts
|

Inharmonic music elicits more negative affect and interferes more with a concurrent cognitive task than does harmonic music

Abstract: We evaluated whether task-irrelevant inharmonic music produces greater interference with cognitive performance than task-irrelevant harm onic music. Participants completed either an auditory (Experiment 1) or a visual (Experiment 2) version of the cognitively demanding 2-back task in which they were required to categorize each digit in a sequence of digits as either being a target (a digit also presented two positions earlier in the sequence) or a distractor (all other items). They were concurrently exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…It is only when auditory roughness is high that perhaps attention is focused on the rough stimulus, in turn mapping on to spiky visual shapes. Such an interpretation would be consistent with Bonin and Smilek (2016) findings on the automatic cognitive interference effect of auditory roughness (from inharmonic chords) in attentional and memory tasks. Interestingly, even though numerous previous studies have shown that higher pitches are typically paired with sharper shapes (e.g., Boyle and Tarte, 1980 ; Marks, 1987 ; Walker et al, 2010 ; Shang and Styles, 2017 ), in the current study, the roughness characteristics of noise predicted of shape design more strongly than the acoustic feature of pitch.…”
Section: Methodssupporting
confidence: 88%
“…It is only when auditory roughness is high that perhaps attention is focused on the rough stimulus, in turn mapping on to spiky visual shapes. Such an interpretation would be consistent with Bonin and Smilek (2016) findings on the automatic cognitive interference effect of auditory roughness (from inharmonic chords) in attentional and memory tasks. Interestingly, even though numerous previous studies have shown that higher pitches are typically paired with sharper shapes (e.g., Boyle and Tarte, 1980 ; Marks, 1987 ; Walker et al, 2010 ; Shang and Styles, 2017 ), in the current study, the roughness characteristics of noise predicted of shape design more strongly than the acoustic feature of pitch.…”
Section: Methodssupporting
confidence: 88%
“…Although researchers had initially found the ACC engaged only during conflict between response representations (Milham et al, 2001;Nelson, Reuter-Lorenz, Sylvester, Jonides, & Smith, 2003;van Veen et al, 2001), which suggested that the ACC could be selectively triggered by such conflicts; successive studies have shown that the ACC can also be engaged during conflicts between other types of semantic and conceptual representations (Badre & Wagner, 2004;van Veen & Carter, 2005;Weissman, Giesbrecht, Song, Mangun, & Woldorff, 2003). Music cognition research has suggested that low tonalness sequences could be inherently conflict-demanding due to their tendency towards equivocal referential tonal centers (Bonin & Smilek, 2016;Huron, 2008;Johnson-Laird, Kang, & Chang, 2012;Krumhansl & Kessler, 1982;Parncutt, 1989Parncutt, , 2011Temperley, 2010), which in turn has been associated with the listeners' experience of increased musical tension (Bigand et al, 1996;Bigand & Parncutt, 1999;Blood et al, 1999;Bravo, Cross, Hawkins, et al, 2017;Lerdahl & Krumhansl, 2007;Schellenberg & Trehub, 1994;Temperley, 2010). We therefore believe that the enhanced activation of the rostral ACC (when comparing dissonant against consonant sequences) could also be explained in terms of conflict monitoring processes.…”
Section: The Acc Role In Conflict Detection and Conflict Resolutionmentioning
confidence: 99%
“…Second, harmonic structure of music may influence cognitive inhibition. Bonin and Smilek (2016) showed that dissonant music elicits greater interferences while completing a cognitive task than harmonic music. As listed in Table 1, tempo, energy, danceability, loudness, valence, and acoustic features of preferred music may influence performance in cognitive tasks (Johansson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%